ComE, an Essential Response Regulator, Negatively Regulates the Expression of the Capsular Polysaccharide Locus and Attenuates the Bacterial Virulence in Streptococcus pneumoniae - Zheng, Yuqiang; Zhang, Xuemei; Wang, Xiaofang; Wang, Libin; Zhang, Jinghui; Yin, Yibing (Frontiers in Microbiology, 2017)
The capsular polysaccharide (CPS) of Streptococcus pneumoniae is the main virulence factors required for effective colonization and invasive disease. The capacity to regulate CPS production at the transcriptional level is critical for the survival of S. pneumoniae in different host niches, but little is known about the transcription regulators of cps locus. In the present study, we isolated and identified the response regulator ComE, the master competence switch in transformation of S. pneumoniae, as a transcriptional regulator of cps locus by DNA affinity chromatography-pulldown, MALDI-TOF mass spectrometry (MS) and electrophoretic mobility shift assay (EMSA). Our results showed that phosphorylated mimetic of ComE (ComED58E) bound specifically to the cps locus prompter in vitro, and phosphorylated ComE negatively impacted both cps locus transcription and CPS production attenuating the pneumococcal virulence in vivo. Compared with D39-WT strain, D39ΔcomE mutant exhibited much thicker capsule, attenuated nasopharyngeal colonization and enhanced virulence in both pneumonia and bacteremia models of Balb/c mice. Furthermore, it was demonstrated that CSP-ComD/E competence system involved in regulating negatively the CPS production during the progress of transformation in D39. Our CSP1 induction experiment results showed that the expression of ComE in D39-WT strain increased powerfully by 120% after 10 minutes of CSP1 induction, but the CPS production in D39-WT strain decreased sharply by 67.1% after 15 minutes of CSP1 induction. However, the CPS production in D39ΔcomE mutant was almost constant during the whole stage of induction. Additionally, we found that extracellular glucose concentration could affect both the expression of ComE and CPS production of D39 in vitro. Taken together, for the first time, we report that ComE, as a transcriptional regulator of cps locus, plays an important role in transcriptional regulation of cps locus and capsular production level.